Sistem Pendukung Keputusan dalam Menentukan Judul Skripsi Mahasiswa dengan Metode WASPAS, COPRAS dan EDAS berdasarkan Penilaian Dosen - Pristiwati Fitriani; Tomy Satria Alasi (STMIK Budi Darma, 2020)
The title of the thesis is the student's scientific exposure. Students are confused about determining the title of the thesis even though the rejected title can be used as learning by other students from the title that has been accepted or has not submitted the title, they do not understand the rules and assessments of all titles when submitted. In addition to this, lecturers related to fields who have researched or studied at a particular Faculty have not been utilized. One student proposes that there are three or more titles, this is very difficult if it is not explained in detail, then if it is rejected, they must submit it again until it is accepted so that it is ineffective and efficient that it must be overcome. This research produces a new technique in submitting a thesis title that is assessed automatically based on the lecturer's assessment, all resolved with a decision support system. Submission of a long thesis title is caused by many factors. Thesis title assessment must be understood by all groups. By adjusting the title with the vision and mission according to the study program. A decision support system is a technique for presenting a decision. In this case the settlement was done by using the WASPAS, COPRAS and EDAS methods. The WASPAS method is to use the compensation method, the attributes are independent, the qualitative attributes are converted into quantitative attributes. The COPRAS method is a normalized decision matrix, a weighted normalized decision matrix, a maximizing and minimizing index, a relative significance value. Then the EDAS method is very practical in conditions with contradictory attributes, and the best alternative is selected by calculating the distance from each alternative from the optimal value. Three methods of filtering and determining the title of the thesis. The criteria for receiving the thesis title are based on the feasibility assessment, renewal, conformity with the vision and mission and academic values associated with the submission of the thesis title. The assessment is also integrated with each lecturer who teaches subjects related to the thesis title. The research method in determining the title of the thesis with quantitative methods. Examining every relationship starting from students, lecturers, thesis titles, criteria related to determining thesis titles. Test all related theories in a measured manner and take test results based on hypotheses. This research produces a complex thesis title determination information system software. comparing the three thesis titles by one of the students, each thesis title has criteria, namely research renewal, vision suitability, mission suitability, student self-grade scores and similarities in existing research, from the results based on the three processed methods obtained